3-Benzyl-Hexahydro-Pyrrolo[1,2-a]Pyrazine-1,4-Dione Extracted From Exiguobacterium indicum Showed Anti-biofilm Activity Against Pseudomonas aeruginosa by Attenuating Quorum Sensing - Singh, Vijay K.; Mishra, Avinash; Jha, Bhavanath (Frontiers in Microbiology, 2019)
Bacterial cell-to-cell communication promotes biofilm formation and can potentially lead to multidrug resistance development. Quorum sensing inhibition (QSI) is an effective and widely-employed strategyagainst biofilm formation. The extract from Exiguobacterium indicum SJ16, a gram-positive bacterium, isolated from the rhizosphere of Cyperus laevigatus showed significant anti-quorum sensing activity (about 99%) against the reference Chromobacterium violaceum CV026 strain without exerting any antibacterial effect. The potentially active QSI compound identified in the SJ16 extract was 3-Benzyl-hexahydro-pyrrolo [1, 2-a] pyrazine-1, 4-dione. The SJ16 extract containing this active compound showed significant anti-quorum sensing activity against a model quorum sensing bacterium strain Pseudomonas aeruginosa PAO1 and a clinical isolate P. aeruginosa PAH by preventing biofilm formation without attenuating the cell growth within the biofilm. More specifically, the SJ16 extract changed the topography and architecture of the biofilm, thus preventing bacterial adherence and further development of the biofilm. Furthermore, it decreased virulence factors (rhamnolipid and pyocyanin), the bacterial motility, as well as the elastase, and protease activities in P. aeruginosa. Microarray analysis revealed the differential expression of quorum sensing regulatory genes. Based on these results, we herein propose a hypothetical model, characterizing the role of this QSI agent in the transcriptional regulation of quorum sensing in P. aeruginosa PAO1, demonstrating that this compound has significant drug-development potential. Further research is required to delineate its possible applications in therapeutics in the context of bio-film forming bacterial infections.